Creating functional groups for analysis of forest data in Palanan, Isabela - Meneses, Angelo C.; Rondon, Ryan Odylon G. (2013)
The Palanan Forest Dynamics Plot has one of the highest biodiversity indices for forests in the Philippines. Nearly 40% of its species are endemic to the country. Previous studies on the Dipterocarpaceae family were used for developing individual based growth models for the species. This research uses per tree and per species methods of clustering to create multiple functional groups specifically for the Palanan plot based on the data from 3 census studies over 12 years. Different combinations of discriminants are also used. The Dipterocarpaceae family remains to be the focus of this study as they are the most dominant. The results of the research are to be used as aids forest management and for developing growth models in the Palanan plot. The methodology and programs used for study can be of use as reference for other forest plots or other families of interest.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Forest management -- Environmental aspects -- Philippines (Isabela); Forest management -- Research -- Philippines (Isabela)